Implementasi Ekstrakurikuler Rohani Islam Sekolah (Rohis) dalam Pembinaan Akhlak Peserta Didik - Dea Delliska Mellsy; Rini Rahman (An-Nuha, 2023)
In the world of education, there is a decline in morals. One of the solutions made to improve the problem of moral decline in the world of education/schools is by implementing school Islamic spiritual extracurriculars (Rohis) in the moral development of students. The purpose of this study was to describe the planning, implementation, and evaluation in implementing school Islamic spiritual extracurriculars (Rohis) in the moral development of students. This research method is descriptive qualitative. In this study, it was found that planning was carried out by the school and spiritual coaches by holding Islamic programs that could foster the morals of students to become akhlakul karimah. The implementation of spiritual extracurriculars in the moral development of students carries out activities with Islamic nuances by establishing four departments namely regeneration, mupalla, syiar and women's affairs. In the evaluation using an approach with the indicator of akhlakul karimah which includes the first three things, morals towards Allah SWT. second, morals towards humans, and third, morals towards nature. The results of this study indicate that the programs implemented in these four departments are able to foster student morals in accordance with good morals.